Cheetah: software for high‐throughput reduction and analysis of serial femtosecond X‐ray diffraction data. (1st June 2014) - Barty, Anton; Kirian, Richard A.; Maia, Filipe R. N. C.; Hantke, Max; Yoon, Chun Hong; White, Thomas A.; Chapman, Henry
<x xml:space="preserve">Abstract</x> The emerging technique of serial X‐ray diffraction, in which diffraction data are collected from samples flowing across a pulsed X‐ray source at repetition rates of 100 Hz or higher, has necessitated the development of new software in order to handle the large data volumes produced. Sorting of data according to different criteria and rapid filtering of events to retain only diffraction patterns of interest results in significant reductions in data volume, thereby simplifying subsequent data analysis and management tasks. Meanwhile the generation of reduced data in the form of virtual powder patterns, radial stacks, histograms and other meta data creates data set summaries for analysis and overall experiment evaluation. Rapid data reduction early in the analysis pipeline is proving to be an essential first step in serial imaging experiments, prompting the authors to make the tool described in this article available to the general community. Originally developed for experiments at X‐ray free‐electron lasers, the software is based on a modular facility‐independent library to promote portability between different experiments and is available under version 3 or later of the GNU General Public License.